Influência da demolição seletiva na redução de impactos ambientais sob a óptica da avaliação do ciclo de vida - Oliveira, Mariana Borges (2024)
The concern about waste generated by demolition processes has driven the search for more sustainable methods for this practice. In Brazil, since the cancellation of ABNT NBR 5682:1977 in 2008, there has been a lack of national normative guidelines addressing the care related to demolition processes and the disposal of generated waste. Improper disposal of construction materials poses risks to human health and the environment due to the presence of toxic substances. Using the concept of circular economy, selective demolition allows for the careful dismantling of materials and construction elements, maximizing their reuse. This technique, aimed at recovering these products through restoration or recycling processes, thereby reduces the environmental impacts associated with this practice. This study presents a comparative analysis between a building constructed with new materials and another constructed with inputs resulting from selective demolition, using the Life Cycle Assessment (LCA) methodology, which evaluates the potential environmental impacts of a product throughout its life cycle. The results of this study indicate that the use of waste from selective demolition can result in a significant reduction in environmental impacts. However, a specific analysis is necessary for each scope, considering various factors, from the processes used in recovery to the quantity allowed and feasible to be used in new products.